Atypical Presentation of COVID-19 Leading to ARDS - Aquino Williams; Lance Alquran; Ummi Khan; Gabriela Bambrick-Santoyo; Roveena Goveas (Case Reports in Infectious Diseases)
A 60-year-old male was brought into the emergency department by EMS after he was found unresponsive by his neighbors. He was initially admitted to the hospital for chronic obstructive pulmonary disease exacerbation secondary to pneumonia. However, due to a sudden, rapidly progressing course of events, the patient was evaluated for COVID-19.